Conversion of methanol to hydrocarbons over zeolite ZSM-23 (MTT): exceptional effects of particle size on catalyst lifetime. Issue 51 (30th May 2017) - Molino, A.; Łukaszuk, K. A.; Rojo-Gama, D.; Lillerud, K. P.; Olsbye, U.; Bordiga, S.; Svelle, S.; Beato, P.
Abstract : A variety of synthetic procedures have been used to obtain zeolite ZSM-23 (MTT) catalysts with crystallite sizes ranging from the micrometer to nanometer scale. Abstract : A variety of synthetic procedures have been used to obtain zeolite ZSM-23 (MTT) catalysts with crystallite sizes ranging from the micrometer to nanometer scale. When the acidic zeolite is used as a catalyst for the methanol to hydrocarbon (MTH) reaction, the catalytic lifetime is dramatically influenced by the crystallite shape and size.